The Use of Phosphate Modified Sago Starch in the making of Fish Ball of the Swangi Fish (Priacanthus tayenus) - Rohaya, Syarifah; harijono, Harijono; Yunianta, Yunianta (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The objectives of this study were to obtain the best of method phosphate modification on sago starch for the making of fish ball of the Swangi fish (Priacanthus tayenus). The research was conducted in two experiments. The first one was a factorial randomized block design experiment with two factors: the types of composite sago starch (CSS made by blending of the natural sago starch (NSS) to the phosphate one (PSS) at various levels (100:0, 75:25, 50:50 and 25:75) and the ratio of the CSS to fish meat apportion of 5%, 10% and 15% respectively. The results indicated that the use of 0.07% STPP produced the best characteristics of phosphate starch intended for the making of fish ball. The PSS, at a moisture content of 9.86%, contains 72.12% starch, 33.07% amylose, 0.38% ash, water absorption index of 525.85%, water solubility index of 0.41%, viscosity of 1020 cps, gel strength of 2.38, Newton the residual phosphor of 0.03%, and the degree of lightness (L value) of 63.23. The best fish ball was obtained by the use of CSS, blended of 25 parts of NSS and 75 parts of PSS, and the fish meat at the ratio of 10%. The fish ball had the following characteristics: 79.42% moisture, 13.59% protein, 0.54% ash, 0.08% fat the texture of 0.014 mm/g/sec, 59.43% of water holding capacity. However, the color of the fish ball made up of PSS-containing CSS was slightly dull. Keywords:Â Sago starch, phosphate modification, fish ball, Priacanthus tayenus